A novel method to estimate the absorption rate constant for two-compartment model fitted drugs without intravenous pharmacokinetic data - Liu, Fan; Yi, Hanxi; Wang, Lei; Cheng, Zeneng; Zhang, Guoqing (Frontiers in Pharmacology, 2023)
The in vivo performances of most drugs after extravascular administration are fitted well with the two-compartment pharmacokinetic (PK) model, but the estimation of absorption rate constant (ka) for these drugs becomes difficult during unavailability of intravenous PK data. Herein, we developed a novel method, called the direct method, for estimating the ka values of drugs without using intravenous PK data, by proposing a new PK parameter, namely, maximum apparent rate constant of disposition (kmax). The accuracy of the direct method in ka estimation was determined using the setting parameters (k12, k21, and k10 values at high, medium, and low levels, respectively) and clinical data. The results showed that the absolute relative error of ka estimated using the direct method was significantly lower than that obtained using both the Loo-Riegelman method and the statistical moment method for the setting parameters. Human PK studies of telmisartan, candesartan cilexetil, and tenofovir disoproxil fumarate indicated that the ka values of these drugs were accurately estimated using the direct method based on good correlations between the ka values and other PK parameters that reflected the absorption properties of drugs in vivo (Tmax, Cmax, and Cmax/AUC0-t). This novel method can be applied in situations where intravenous PK data cannot be obtained and is expected to provide valuable support for PK evaluation and in vitro-in vivo correlation establishment.